Respuesta :

Answer:

Solve the rational equation by combining expressions and isolating the variable  

x = ln ( t − √ t ^2 + 4  )/2

x = ln ( t +√ t ^2 + 4  )/2

Answer:

Step-by-step explanation:

I assume that the equation is

[tex]e^x+\frac{e^{-x}}{e^x} -e^{-x}=t \\[/tex]

[tex]e^x+\frac{1}{e^{2x}}-\frac{1}{e^x} = t[/tex]

[tex]e^{3x}+1-e^x=e^{2x}t[/tex]

[tex]e^{3x}-te^{2x}-e^x=-1[/tex]

Let u = e^x

[tex]u^3-tu^2-u=-1[/tex]

[tex]u(u^2-tu-1) = -1[/tex]

if u=1, then [tex]u^2-tu-1 =-1 \longleftrightarrow u^2-tu=0[/tex]

then u = 0 (reject) or u = t

So far, we have u = 1 and u = t

if u =1, e^x =1 , then x = 0

if u = t, then e^x = t or x = lnt

ACCESS MORE